Review Of Theories And Models Of Economic Growth - Piętak, Łukasz (Comparative Economic Research. Central and Eastern Europe, 2014)
The subject of this article is a review of the theories and models of economic growth. In the first section, the author analyzes the theories of economic growth, such as Schumpeter’s, Lewis’s and Rostow’s theory. In the second part there is a review of the models of economic growth. In this part the author divides models into two groups: exogenus models and endogenus models. The article finishes with conclusions concerning the issues discussed. The method used in writing the article is an analysis of the English and Polish literature on the subject.